A brief history of the Department of Animal Sciences and Industry at Kansas State University - McKee, Miles (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
The Department of Animal Sciences and Industry at Kansas State University celebrates its 100th anniversary this year. This review outlines some of the key historical moments in its development.
Keywords: Beef; History